ANALISIS KEPEMIMPINAN CAMAT DALAM RANGKA MENINGKATKAN DISIPLIN KERJA APARATUR PEMERINTAH DI KECAMATAN MUARA TABIR KABUPATEN TEBO - Hane Johan (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2015)
The aim of this study is to know the influence of the leadership of the head Of against government agencies work discipline the of the sub Muara Tabir of archipelago Tebo regency, related by indicator of each Variables. The indicator of the council’s leadership are, the decision making of the council’s, giving motivation, the ability of the council’s in enforcing the regulation and become a good example. While the indicator of the officials discipline are to identity the discipline of official on responsibility when working, ambition or spirit to work, obedience to the rule, and to use and to keep the office facilities with care. The factors influencing the discipline of apparatus will also be explained.Data is collected through the quiz, interview and document analysis. The is a correlation study involving two variables which include the leadership of council and discipline of government  agencies work discipline the of the sub Muara Tabir. Descriptive analysis is used. Population includes all government official in the Muara Tabir sub district. Sample include 13 (thirteen) people, head is placed as an informant along with members of the public as much as 8 (eight) people who never do administrative affairs the Office of subdistrict  Muara Tabir  Tebo Islands.The result of this study indicates that the leadership of the head of Muara Tabir role and influence in fostering discipline particularly of sub-district and Muara Tabir generally in the community. However, the awareness of every individual direct acting as government agencies, state servant and community servant are the main element to build discipline optimally, it is also influenced by many other factors which are individually motivation Government agencies of any such.